Predictive Value of Neutrophil-to-Lymphocyte Ratio on Hospital Mortality of Patients with Community-Acquired Pneumonia - Islam, Md Khairul; Hossain, Zakir; Hossain, Fahima Sharmin; Alam, Nur; Rahman, Abul Kalam Md Sajedur; Rashid, Md Mamunur; Aziz, Mohammad Zakaria Al; Zaman, Md Monir Uz (Journal of Medicine, 2025)
Background: The neutrophil-to-lymphocyte ratio (NLR), a cheap blood parameter, has shown promise as a predictor of adverse outcomes in severe infections. However, its utility in predicting mortality among patients with severe CAP in Bangladesh remains underexplored. Objective: This study aimed to assess the predictive value of admission NLR for in-hospital mortality among patients with CAP admitted to a tertiary care hospital in Bangladesh. Methods: This prospective, observational study was conducted from July 2023 to June 2024 at Dhaka Medical College Hospital. One hundred eight patients aged 18 years or older with a clinical and radiological diagnosis of CAP were included. Exclusion criteria were hospital-acquired pneumonia, pulmonary tuberculosis, malignancy, immunosuppression, and HIV infection. Baseline demographic, clinical, and laboratory data were collected. NLR was calculated from routine complete blood counts, and a predefined cutoff of 7.12 was used for stratification. In-hospital mortality was the primary outcome. Logistic regression and ROC curve analyses were performed to evaluate the predictive performance of NLR. Results: The overall in-hospital mortality rate was 12.0%. Patients with an NLR ³7.12 had a significantly higher mortality risk (OR: 1.63; 95% CI: (1.07–3.82); p = 0.040). Multivariate analysis identified NLR as an independent predictor of mortality (adjusted OR: 1.34; 95% CI: 1.02–1.75; p = 0.033), along with chronic kidney disease (adjusted OR: 5.63; 95% CI: 1.15–27.60; p = 0.033) and cardiac failure (adjusted OR: 36.87; 95% CI: 5.57–244.22; p < 0.001). ROC analysis demonstrated excellent predictive performance for NLR, with an area under the curve (AUC) of 0.905. Conclusion: Elevated admission NLR is a significant independent predictor of in-hospital mortality in patients with CAP. Given its simplicity, cost-effectiveness, and widespread availability, NLR can be a valuable prognostic tool in resource-constrained settings, complementing traditional clinical scores like CURB-65. J MEDICINE 2025; 26(2): 110-116